The Influence of Realia Model Learning Media on Geography Learning Outcomes in Knowing the Earth Material - Permatasari, Intan (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study aims to determine the effect of the realia model of learning media on geography learning outcomes in class X IIS students on the subject of knowing the earth. Methodology: This study used a quantitative method with an experimental approach. The population in this study were all class X IIS SMA Negeri 22 Jakarta consisting of 4 classes of 144 students. The sampling technique was carried out by purposive sampling, which is based on the grades of the geography subject. The lowest score was obtained in class X IIS 1 and X IIS 2 with an average value of 74.38. The sample used was 72 students, consisting of 2 classes, namely class X IIS 1 as an experimental class of 36 students and class X IIS 2 as a control class of 36 students. The research was conducted in 5 meetings with a time allocation of 3 x 45 minutes each. The instrument used in this study was in the form of multiple choice tests totaling 24 questions. The researcher used instrument tests in the form of validity and reliability tests. After the data was collected, the researcher conducted a requirements test data by normality and homogeneity tests. The data analysis technique used the Paired Sample T-test to test the hypothesis. In processing the data the researchers used SPSS version 16.0. Main Finding: The results of the calculation of the hypothesis test using the Paired Sample T-test obtained the value of –t count < -t table (-12,142 <-2,030) and Sig (2-tailed) 0,000 with α 0,025, so it can be said Sig (2-tailed) 0,000 < α (0.025) which means Ho is rejected. This means that there is an influence of the realia model of learning media on geography learning outcomes in the subject of knowing the earth at SMA Negeri 22 Jakarta. Novelty/Originality of this study: Applying realia model learning media in geography learning activities in an effort to improve student learning outcomes.